Front Cover: Amperometric Detection of dsDNA Using an Acridine‐Orange‐Modified Glucose Oxidase (ChemPlusChem 11/2017). Issue 11 (18th September 2017) - Jambrec, Daliborka; Lammers, Klaus; Bobrowski, Tim; Pöller, Sascha; Schuhmann, Wolfgang; Ruff, Adrian
Abstract : The cover picture shows a novel procedure for the preferential post‐hybridization labeling of double‐stranded DNA based on the intercalating compound acridine orange, which was covalently bound to glucose oxidase. Labeling with a highly active biocatalyst allows for a simple and sequence‐independent amplification of the signal proportional to the amount of hybridized DNA that may be coupled with other amplification strategies. Details are given in the Communication by D. Jambrec et al. onpage 1311 in Issue 11, 2017 (DOI:10.1002/cplu.201700279 ).